New design model for brittle failure in the parallel-to-grain direction of timber connections with large diameter fasteners. (15th August 2020) - Yurrita, Miguel; Cabrero, José Manuel
Highlights: Brittle failure modes may happen in timber connections loaded parallel-to-grain. A new model for brittle failure in joints with large diameter fasteners is proposed. As a design model, it aims to be clear and simple for designers. The new proposal improves the accuracy of the existing models. Abstract: Timber connections may collapse in a brittle or in a ductile mode. The calculation models of timber joints are mainly focused on ductile failure mode, since it has been traditionally assumed that brittle failure was avoided by respecting a minimum spacing between fasteners. However, this assumption alone does not guarantee a ductile failure. This paper proposes a new design model dealing with brittle failure modes of timber connections with large diameter fasteners (those protruding the whole thickness of the timber member such as dowels or bolts). A comparison between the proposal and the existing models, using an extensive database of tests, is used to demonstrate the improved accuracy of the proposed design method.